Emulsion gels formed by electrostatic interaction of gelatine and modified corn starch via pH adjustments: potential fat replacers in meat products - Asyrul-Izhar, Abu Bakar; Bakar, Jamilah; Sazili, Awis Qurni; Goh, Yong Meng; Ismail-Fitry, Mohammad Rashedi (Multidisciplinary Digital Publishing Institute, 2023)
The application of emulsion gels as animal fat replacers in meat products has been focused on due to their unique physicochemical properties. The electrostatic interaction between proteins and polysaccharides could influence emulsion gel stability. This study aimed to evaluate the physicochemical properties of emulsion gels using starch and gelatin as stabilizers, promoting electrostatic attraction via pH adjustment. Three systems were studied: emulsion gel A (EGA) and emulsion gel B (EGB), which have positive and negative net charges that promote electrostatic interaction, and emulsion gel C (EGC), whose charge equals the isoelectric point and does not promote electrostatic interactions. There was no significant difference in proximate analysis, syneresis and thermal stability between samples, while EGA and EGB had higher pH values than EGC. The lightness (L*) value was higher in EGA and EGB, while the yellowness (b*) value was the highest in EGC. The smaller particle size (p < 0.05) in EGA and EGB also resulted in higher gel strength, hardness and oxidative stability. Microscopic images showed that EGA and EGB had a more uniform matrix structure. X-ray diffraction demonstrated that all the emulsion gels crystallized in a β′ polymorph form. Differential scanning calorimetry (DSC) revealed a single characteristic peak was detected in both the melting and cooling curves for all the emulsion gels, which indicated that the fat exists in a single polymorphic state. All emulsion gels presented a high amount of unsaturated fatty acids and reduced saturated fat by up to 11%. Therefore, the emulsion gels (EGA and EGB) that favored the electrostatic protein-polysaccharide interactions are suitable to be used as fat replacers in meat products.